Activation Energy, Temperature Coefficient and Q10 Value Estimations of the Growth of an SDS-degrading Bacterium - Rahman, Mohd Fadhil; Manogaran, Motharasan; Yakasai, Hafeez Muhammad; Abubakar, Aisami (Journal of Environmental Microbiology and Toxicology, 2023)
This research delves into how temperature affects the growth rates of bacteria in relation to the breakdown of sodium dodecyl sulfate (SDS) by types of microbes. A graph resembling a Chevron pattern, which plots the growth rate against temperature (1/T), revealed a change at 32.19 °C, indicating a crucial temperature for optimizing bacterial growth. Through regression analysis, activation energies were determined to be 65.10±10.83 kJ/mol for temperatures between 20 30°C and 36.31±0.97 kJ/mol for temperatures between 35 45°C showing that metabolic demands are higher at temperatures. The theta value was calculated to be 1.06, which closely aligns with known values for processes hinting at moderate temperature sensitivity. These results highlight the impact of temperature on microbial metabolic efficiency, requiring energy at lower temperatures due to increased enzyme activity demands while operating more efficiently at higher temperatures with lower energy needs. This study emphasizes incorporating temperature-related factors like Q10 and theta values into models that predict bioremediation strategies. Understanding these dynamics can improve the success of bioremediation efforts by ensuring breakdown in diverse environmental conditions. The insights gained from this research can inform management practices. Advance the development of biotechnological applications sensitive to temperature variations.